Evaluation of human embryonic stem cells and their differentiatedfibroblastic progenies as cellular models for in vitro genotoxicity screening - Vinoth, Kumar Jayaseelan; Manikandan, Jayapal; Sethu, Swaminathan; Balakrishan, Lakshmidevi; Heng, Alexis Boon Chin *; Lu, Kai; Hande, Manoor Prakash; Cao, Tong (Elsevier, 2014)
This study evaluated human embryonic stem cells (hESC) and their differentiated fibroblastic progeniesas cellular models for genotoxicity screening. The DNA damage response of hESCs and their differentiated fibroblastic progenies were compared to a fibroblastic cell line (HEPM, CRL1486) and primary cultures of peripheral blood lymphocytes (PBL), upon exposure to Mitomycin C, gamma irradiation and H2O2. It was demonstrated that hESC-derived fibroblastic progenies (H1F) displayed significantly higher chromosomal aberrations, micronuclei formation and double strand break (DSB) formation, as compared toundifferentiated hESC upon exposure to genotoxic stress. Nevertheless, H1F cell types displayed comparable sensitivities to genotoxic challenge as HEPM and PBL, both of which are representative of somatic cell types commonly used for genotoxicity screening. Subsequently, transcriptomic and pathways analysis identified differential expression of critical genes involved in cell death and DNA damage response upon exposure to gamma irradiation. The results thus demonstrate that hESC-derived fibroblastic progenies are as sensitive as commonly-used somatic cell types for genotoxicity screening. Moreover, hESCs have additional advantages, such as their genetic normality compared to immortalized cell lines, as well as their amenability to scale-up for producing large, standardized quantities of cells for genotoxicity screening on an industrial scale, something which can never be achieved with primary cell cultures.